The Impact of Error in Persona: Liability of Police Investigators in Cases of Wrongful Arrests - Tasya, Amalia (Journal of Strafvordering Indonesian, 2024)
Errors in arrest, known as "errors in persona," are one of the fundamental problems in the criminal justice system that demands serious attention. This phenomenon not only reflects the failure of law enforcement officials to carry out their duties, but also raises various adverse implications, both for individuals who are victims of wrongful arrest and for public trust in the integrity of the legal system. In a country of law that prioritizes the principles of justice and legal certainty, errors in arrest are serious challenges that can injure these basic principles. Police investigators, as one of the main actors in the law enforcement process, play a very vital role in ensuring that any action taken is in accordance with applicable legal procedures. They are responsible for making arrests, detentions, and investigations based on sufficient evidence and with regard to human rights. However, in reality, in practice mistakes often occur that lead to the arrest of innocent people. These mistakes can occur due to a variety of factors, including a lack of adequate evidence, pressure to resolve cases quickly, errors in suspect identification, or even practices that violate the ethics of investigator professionalism. Errors in person not only have an impact on the victims who are directly affected, such as psychological trauma, social stigma, and material loss, but also have broader legal consequences. This mistake can damage the credibility of law enforcement officials, create public distrust, and ultimately erode the legitimacy of the legal institution itself. In a broader context, error in persona also interferes with the principle of justice that should be the main foundation in the criminal justice system. This study aims to analyze the impact of error in persona with a special focus on the accountability of police investigators in cases of wrongful arrest. This research will examine how the accountability mechanism of investigators is regulated in the Indonesian legal system, as well as how the rules are applied in various concrete cases. In addition, this research will also explore the legal aspects that govern protection for victims of wrongful arrest, including recovery and compensation mechanisms, as well as an evaluation of the effectiveness of existing regulations. One of the important issues that will be discussed is the extent to which investigators can be held legally accountable, both criminally, civilly, and administratively, when an arrest is made. In this case, the study will highlight whether the current regulations are adequate to hold investigators accountable, or whether there are still legal loopholes that allow investigators to escape responsibility for the mistakes that occurred. Furthermore, this study will also discuss the social and psychological implications of error in persona, especially how the public views cases of wrongful arrest and its impact on public trust in law enforcement officials. Thus, this research is expected to make a significant contribution to the development of better legal policies, as well as provide constructive recommendations to prevent the recurrence of arrest errors in the future.